ULTRASOUND GUIDED ASPIRATION VERSUS DRAINAGE UNDER GENERAL ANESTHESIA IN BREAST ABSCESSES (Iraqi Journal of Medical Sciences, 2016)
Background:Despite the fact that breast abscess is becoming less common in developed countries, it has remained one of the leading causes of morbidity in women in developing countries. Ultrasound has been shown to be useful in diagnosis of breast abscesses, guiding needle placement during aspiration and also enables visualization of multiple abscess loculation and thus useful in needle aspiration of breast abscesses and is associated with less recurrence, excellent cosmetic result and has less cost.Objective:To establish whether ultrasound guided needle aspiration is a feasible alternative treatment option for breast abscesses.Methods: A prospective interventional study conducted on 144 female patients with and age range from 15 to 55 years. One hundred and twenty four are lactating and the other 20 are non-lactating. They were divided into two groups; the first group comprised 72 patients treated as outpatients by ultrasound assisted aspiration of pus while the second group serves as the control comprised 72 patients who are treated by drainage under general anesthesia. For both groups, data regarding early complications, hospital stay, return to daily activity and late complications were recorded. Follow up for up to 3 months was done for both groups.Results:Healing rate of the two groups had no statistically significant difference both overall and at each visit. There was only 1.4% recurrence rate observed in the ultrasound guided needle aspiration group while there was 6.9% recurrence rate observed in the incision and drainage group.Conclusion: Sonographically guided percutaneous aspiration of breast abscesses represents a less invasive and very promising alternative to surgical incision, showing the following advantages: no general anesthesia required a superior cosmetic result and shorter hospitalization.Key words:Breast abscess, Ultrasound guided aspiration, Incision and drainage
Keywords: Breast abscess; Ultrasound guided aspiration; Incision and drainage